(untitled) (International Journal of Built Environment and Sustainability, 2020)
The use of urban green space is a determinant for urban inhabitant’s well-being. However, increasing urbanisation lessened the opportunity for urban inhabitants to engage with green space. This situation requires landscape planners to design an urban green space with maximum benefits that fulfil inhabitants’ needs for their well-being. Structural biodiversity is an essential element in generating the benefits and values interpreted through the activities at the urban green space. This paper aims to identify the cultural practices that influenced by structural biodiversity of two urban forests in Johor Bahru, Malaysia. Multiple Response Analysis was used to analyse the data from on-site questionnaire surveys completed by 253 visitors of both urban forests. The result shows that a high-density urban forest offers an opportunity for visitors to get attached to nature and attract visitors to involve in sedentary and moderate activities. In contrast, a moderate density urban forest offers a less natural value that attracts visitors to take part in moderate and vigorous activities with less engagement with nature. This study would contribute to a better understanding of the structural biodiversity that influenced visitors’ cultural practices, where the present condition of the two urban forests has illustrated the current benefits that visitors obtained from the ecosystem.